2015
DOI: 10.1007/jhep06(2015)043
|View full text |Cite
|
Sign up to set email alerts
|

A note on AdS cosmology and gauge theory correlator

Abstract: Using AdS/CFT prescription, we compute two point Yang-Mills correlator on a constant time slice for the Kasner background. Pushing the surface close to the initial singularity, we find, in some cases, the correlator does not develop pole. We further numerically calculate similar correlator where the bulk is a Kasner AdS soliton. We find that the qualitative behaviour of the correlator remains unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…This implies that for t > 0, the turning point occurs at t * = (−c) −1/2p . The function x(t) can be obtained from u(t) by direct integration; the result below agrees with the earlier work of [16]: 3…”
Section: Jhep07(2015)044supporting
confidence: 89%
See 1 more Smart Citation
“…This implies that for t > 0, the turning point occurs at t * = (−c) −1/2p . The function x(t) can be obtained from u(t) by direct integration; the result below agrees with the earlier work of [16]: 3…”
Section: Jhep07(2015)044supporting
confidence: 89%
“…We conclude this section by treating the separate case in which p = − 1 2n+1 . By setting p = − 1 2n+1 in the equations of motion (3.5), we may implement a variable redefinition y = −t −2p c −1 , which allows us to obtain a solution for these particular values of p via the same methodology described above: 16) where the constants c 3 and c 4 are determined as above:…”
Section: Jhep07(2015)044mentioning
confidence: 99%
“…It was found that if the direction along which the operators were separated carries a negative Kasner exponent, the correlators developed divergences in their IR. Subsequently, in [15], by solving the space-like geodesic equations for arbitrary exponents, it was noticed that for correlators separated along the positive Kasner exponents, correlation vanishes even if one pushes the space-like surface close to the singularity. While the reason for such behaviour is not yet obvious to us, in the present work we consider a larger class of time dependent geometries in AdS, study their symmetries, embeddings in flat space of higher dimensions, space-like geodesics in the geometries and nature two point correlators at the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…In [15] a more general solution where the D3-brane worldvolume is replaced by Friedmann-Robertson-Walker (FRW) metric with a conformal factor was obtained and its properties were analyzed [16]. For the M5-brane only the Kasner deformation has been investigated [17,18].…”
Section: Introductionmentioning
confidence: 99%